Gênero e educação em Moçambique : acesso e permanência da mulher rural no ensino superior - Tambe, Telma Amorgiana Fulane (2023)
Mozambique has been experiencing reforms in its public policies that establish a parallel between global marketing policies and new ways of modeling the subject to respond to market demands that have been taking place throughout most of the world. These are discourses of “inclusion of all”, intertwined with hegemonic discourses that intend to include a right of all for all. Thus, with this study we intend to understand the strategies of access and permanence in higher education by rural women in Mozambique, questioning the conditions of access and permanence of women in higher education. In particular, we intend to analyze the access and permanence strategies in HE used by women in Mozambique, focusing on those from rural areas. The research has as object of study strategies used by rural women in accessing and staying in public HE in Mozambique. For this purpose, we opted for a qualitative approach (MINAYO, 1992, 2002; GERHADT et al, 2009), anchored in Discourse Analysis. We also chose to study texts on educational policies (BALL; BOWE, 1992; BALL and MAINARDES, 2006; NKRUMAN, 1977, AFIGBO, 2010; GARCIA, 2005, GONÇALVES, 2018), literature on feminism (CASIMIRO, 2014; PERROT, 2003, 2005; HILDETE, 2018; AMARAL, 2010; GONZALÉZ, 2006, 2015, GUERRA, 2013, SEGATO, 2012), articulated to Political History and Cultural History (CHARTIER, 2002; GEERTZ, 1989). our findings point out that one of the main challenges for women's access and permanence in HE is the little amount of information they have or accumulate about the university world and policies inherent to it; they also count their social class, race/ethnicity, origin and culture. However, these black women, inserted in a patriarchal, sexist, capitalist structure, have built access and permanence strategies: sociability networks, admission exams, business, scholarships, among others.